Ultrathin ionic liquid films on metal surfaces: adsorption, growth, stability and exchange phenomena - Lexow, Matthias; Maier, Florian; Steinrück, Hans-Peter (Advances in Physics: X, 2020)
The interface of ionic liquids (ILs) with solid surfaces is of pivotal interest for many applications, ranging from sensors, lubrication, separation technology, and electronics to electrochemistry and catalysis. We present a short review on ultrathin layers of ionic liquids on metal surfaces using a surface science approach. We mainly focus on specific examples of imidazolium-based ionic liquids on Ag(111) and Au(111) studied by angle-resolved X-ray photoelectron spectroscopy, and relate the obtained results to existing literature. We address a variety of phenomena on the molecular level, namely, (i) the adsorption, growth and wetting behavior of ILs, (ii) the thermal stability and desorption of ILs, (iii) exchange processes of anions and cations at the IL/solid interface, and (iv) the replacement of ILs from the IL/solid interface by porphyrins.
CRIS-Team Scopus Importer:2020-07-31
Keywords: growth mode; Ionic Liquids; liquid/solid interface; surface Science; X-ray photoelectron spectroscopy